2011
DOI: 10.1007/s12640-011-9246-y
|View full text |Cite
|
Sign up to set email alerts
|

Higher Aluminum Concentration in Alzheimer’s Disease After Box–Cox Data Transformation

Abstract: Evidence regarding the role of mercury and aluminum in the pathogenesis of Alzheimer's disease (AD) remains controversial. The aims of our project were to investigate the content of the selected metals in brain tissue samples and the use of a specific mathematical transform to eliminate the disadvantage of a strong positive skew in the original data distribution. In this study, we used atomic absorption spectrophotometry to determine mercury and aluminum concentrations in the hippocampus and associative visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 20 publications
(20 reference statements)
1
27
0
Order By: Relevance
“…In this study, we demonstrate that AlCl 3 induces toxic fibrillar Aβ aggregation in cortex and hippocampus of mice brain. Moreover documented reports denote that aluminium was specifically deposited in cortex and hippocampal regions of AD patients and also in rodents exposed to aluminium [33,34,35]. These reports support documented report denotes that Amyloid-β 42 induces neuronal cell death via ASK-1 [36] and JNK activation [37].…”
Section: Discussionsupporting
confidence: 79%
“…In this study, we demonstrate that AlCl 3 induces toxic fibrillar Aβ aggregation in cortex and hippocampus of mice brain. Moreover documented reports denote that aluminium was specifically deposited in cortex and hippocampal regions of AD patients and also in rodents exposed to aluminium [33,34,35]. These reports support documented report denotes that Amyloid-β 42 induces neuronal cell death via ASK-1 [36] and JNK activation [37].…”
Section: Discussionsupporting
confidence: 79%
“…The 27 subjects (12 women and 15 men, mean age 76 years) in the referent group had no signs of AD or other degenerative dementias on autopsy. Different statistical approaches used by Rusina et al (2011) provided somewhat different results: higher mean Al concentrations in the hippocampus were found in AD patients compared with the healthy individuals (0.357 vs 0.090 μg/g; p = 0.039) after Box-Cox data transformation, but not after standard logarithmic transformation to correct deviations from normality.…”
Section: Organ Systems and Functionmentioning
confidence: 96%
“…Rusina et al (2011) measured Al in brains from 29 deceased patients (mean age 79 years, women to men ratio 20:9) with neuropathologically confirmed AD. All these samples fulfilled the National Institute of Aging (Hyman et al 2012, McKhann et al 2011) and Reagan Institute (Newell et al 1999) AD diagnostic criteria.…”
Section: Organ Systems and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that Co -, Cr -, and Mo -ions are considered toxic, carcinogenic and also able to promote inflammation (Andrews et al, 2011;Hinüber et al, 2010;Jakobsen et al, 2007). Aluminum is also considered to be a risk factor for the pathogenesis of Alzheimer's disease (McLachlan et al, 1990;Rusina et al, 2011). However, Ti-6Al-4V has an advantage over Co-28Cr-26Mo because of the presence of Vanadium.…”
Section: Introductionmentioning
confidence: 99%